Relationship between neurocognition and theory of mind as a function of symptomatic profile in schizophrenia: results from the national FACE-SZ cohort. Issue 1 (2nd January 2022) - Rambeau, Sébastien; Del Goleto, Sarah; Pignon, Baptiste; Lajnef, Mohamed; Petrucci, Jean; Szöke, Andreï; Fond, Guillaume; Lançon, Christophe; Dorey, Jean-Michel; Rey, Romain; Garbisson, Amandine; Capdevielle, Delphine; et al.
ABSTRACT: Introduction: Deficits in theory of mind (ToM) can vary depending on the predominant schizophrenia symptoms, and though most neurocognitive functions are involved in ToM, all may not be associated with the same symptoms. With consideration to the relationships between symptoms, neurocognition and ToM, the aim of the present study is to identify the neurocognitive functions influencing ToM capacities according to symptomatic profile. Methods: The study is based on a sample of 124 adults with schizophrenia from a French national cohort. Patients were divided into two groups according to their scores on the five Wallwork factors of the Positive and Negative Syndrome Scale using hierarchical clustering before carrying out multivariable analyses. Results: The "disorganised group" ( n = 89) showed high scores on the disorganised factor, and had a ToM associated with reasoning, visual recognition and speed of processing . The "positive group" ( n = 35) showed high scores on the positive and depressive factors, and had a ToM associated with working memory . Conclusions: These results suggest that neurocognitive predictors of ToM in schizophrenia are different according to the predominant clinical dimension, thus refining our knowledge of the relationship between symptoms, neurocognition and ToM, and acknowledging their status as important predictors of patients' functional status.